Upaya Meningkatkan Penguasaan Senam Ketangkasan Melalui Pendekatan Bermain dan Media Bantu dalam Pembelajaran Penjasorkes bagi Siswa SD Negeri 44 Ampenan - Komalasari Komalasari (UNDIKMA, 2020)
This study aims to improve mastery of dexterity gymnastics through playing approaches and assistive media in physical education learning for students. This research method uses a classroom action research method with research subjects namely students of class II SD Negeri 44 Ampenan. The research instrument used observation, interviews, and tests. The data analysis technique used in this research was qualitative and quantitative descriptive analysis. The results of this study indicate that the play approach and assistive media can increase interest, activeness, and dexterity gymnastics for the second grade students of SD Negeri 44 Ampenan.